A clinical comparison of an endothelin receptor antagonist and phosphodiesterase type 5 inhibitors for treating digital ulcers of systemic sclerosis. (12th February 2021) - Chang, Sung Hae; Jun, Jae Bum; Lee, Yun Jong; Kang, Tae Young; Moon, Ki Won; Ju, Ji Hyeon; Kang, Seong Wook; Choi, In Ah; Park, Yong-Beom; Lee, Seung Geun; Lee, Shin-Seok; Heo, Nam Hun; et al.
Abstract: Objectives: To assess the efficacy of an endothelin receptor antagonist (ERA) and phosphodiesterase type5 inhibitors (PDE5is) for treating SSc-related digital ulcers (DUs). Methods: This prospective, multicentre, observational cohort study recruited patients with active SSc-related DUs from 13 medical centres in South Korea. The primary outcome was time to cardinal ulcer (CU) healing. A secondary outcome was time to new DU occurrence. Patients were followed up 4, 8, 12 and 24 weeks after treatment initiation. Results: Sixty-three patients were analysed. Their mean age was 49.9 years (s .d . 11.4) and 49 were female. Twenty-eight had limited SSc. Forty-nine patients received ERA, 11 received a PDE5i (9 sildenafil, 1 udenafil and 1 tadalafil) and 3 received other medication. The hazard ratio (HR) for time to CU healing in the ERA group vs the PDE5i group was 0.75 (95% CI 0.35, 1.64; P  = 0.47) in an unadjusted model and 0.80 (95% CI 0.36, 1.78; P  = 0.59) in a model adjusted for age, sex, use of calcium channel blockers (CCBs), total DU number and initial CU area. The HR for new DU development in the ERA group vs the PDE5i group was 0.39 (95% CI 0.16, 0.93; P  = 0.03) in an unadjusted model and 0.32 (95% CI 0.13, 0.81; P  = 0.02) in an adjusted model. No patients receiving CCBs developed new DUs at 24 weeks. Conclusion: Time to CU healing is comparable for ERA and PDE5i. ERAs are more effective in reducing new DU occurrence than PDE5is. CCBs may be effective as a background medication.